Evaluation of crosslinking degree on the characteristics and performance of membranes formulated from quaternized chitosan / Abdul Aziz Mohd. Nasir, Norin Zamiah Kassim Shaari, Nur Syazwanie Izzati Chik - Mohd. Nasir, Abdul Aziz; Kassim Shaari, Norin Zamiah; Chik, Nur Syazwanie (Universiti Teknologi MARA Shah Alam, 2023)
Chitosan is a polymer produced from chitin that is insoluble in neutral or basic pH conditions. Although chitosan has good biodegradability, nontoxicity, and biocompatibility properties, it has limited applications due to its low solubility in neutral or slightly alkaline conditions. Quaternization came out as a way of altering this natural polymer to enhance its solubility over a wide pH range and boost permanent positive charges. In this study, the quaternized chitosan (QCs) was prepared by using 3-chloro-2-hydroxypropyltrimethyl ammonium chloride (CHTAC) as the quaternizing agent, which was then formulated into the integral membrane with a blend of polyvinyl alcohol (PVA), polysulfone (PSF), and tetraethylorthosilicate (TEOS). The membrane characterizations and performance analysis were done in terms of functional groups, surface charge, surface morphology, pure water flux analysis, and antifouling analysis. The results revealed that the incorporation of TEOS produced a dense membrane structure but did not help much in enhancing the hydrophilicity and the positive charge of membranes. Membrane from the polymer blend without TEOS was found to have better hydrophilicity, and antifouling characteristics in terms of relative flux recovery (RFR) and relative flux decay (RFD) and possessed a slightly negative charge. The dense structure of the membrane due to crosslinking process might result in a high degree of integral stability, with the additional benefit of providing more adsorption area for a potential application in the heavy metal ion removal process.